Responding to politically motivated migration pressure: how Latvia and Poland addressed the migration crisis on their borders with Belarus in 2021 - Grauda, Grēta (Riga Graduate School of Law, 2024)
In the summer of 2021, the situation on the European Union’s eastern border with Belarus deteriorated rapidly with thousands of migrants, mainly, from the MENA countries gathering at the borders between Belarus and three Member States - Latvia, Lithuania, and Poland – looking forward to entering their territory. The Union believes it to be a “hybrid attack” launched by the authoritarian regime of Lukashenko. The main aim the author of this paper tries to achieve, however, is to prove that such a formulation of the events on these borders is inadequate and is the reason why great violations of the fundamental rights of these migrants by two target states: Latvia and Poland occurred. Not only the author of this paper analyses the nature of the particular migrant flow but also suggests a more appropriate way to refer to these events, ensuring the compliance with key principles of international migration law.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Migration; Refugees; Non-refoulement; Latvia; Belarus; Poland